Analysis Of Liquifaction Potential Using The Method Microzonation in Coastal Zone at North Aceh District - Deassy Siska; Ahmad Nayan; Sofyan Sofyan; M. Fauzan; Mukhlis Mukhlis (LPPM Universitas Malikussaleh, 2022)
Liquefaction is a natural phenomenon that occurs when previously sandy soil turns into mush as a result of an earthquake and has the potential to become a natural disaster if not anticipated early. the coastal zone of Dewantara District is included in the earthquake-prone area (referring to the results of previous studies, the value of the seismic vulnerability index is between 0.41 to 18.3 Kg, with the potential for damage caused to be medium and high risk) because most of the area is an area that has alluvial plains a wide beach and located on a tectonic route so that it is estimated that there is a potential follow-up threat after an earthquake occurs, in the form of liquefaction. Determination of the distribution of liquefaction potential due to earthquakes is determined based on data obtained from microtremor measurements. The specific objective of this study is to provide information regarding the potential and vulnerability of liquefaction to Policy Makers/Local Governments in evaluating plotting areas and/or preparing regional spatial plans based on disaster risk reduction/mitigation aspects. Based on the results of the processed data analysis, several important conclusions can be identified in this study. The character of soil vulnerability is related to the value of dominant frequency (f0), soil amplification (A0), and seismic vulnerability index (seismic vulnerability index). This relationship can be used to formulate whether an area has the potential to experience lateral ground motion (liquefaction) which potentially can affect the coastal area of ​​Dewantara District. Based on microseismic data analysis (standard deviation), several disaster-prone zone points were obtained in the north and east of the measurement point. In detail, this is shown by the map of the distribution of SVI values ​​in the Coastal Area which is in the range of 20-100, especially in the north it is at a value above 75, which allows for a higher chance of liquefaction on the condition that there are major earthquakes accompanied by with rock pores filled with fluid.